Taxonomic treatments of Pyrenaria jonquieriana (Theaceae) and related taxa - Yang, Ye-Kun; Zhang, Qiong; Ma, Jin-Lin; Yang, Shi-Xiong (Phytotaxa, 2021)
On the basis of field investigation and herbarium specimen examination,  Tutcheria multisepala, Pyrenaria poilaneana, Parapyrenaria indochinensis and Camellia luuana are treated to the synonymy of Pyrenaria jonquieriana. In addition, lectotypes are designated for the names Pyrenaria jonquieriana and Pyrenaria poilaneana.